PENERAPAN PERAWATAN LUKA DENGAN GEL ALOEVERA UNTUK MENGATASI GANGGUAN INTEGRITAS KULIT DAN JARINGAN PADA PASIEN ULKUS KAKI DIABETIK - Meira Budyati; Hariawan Junardi (JKM-Bid: JURNAL KESEHATAN MASYARAKAT KEBIDANAN (The Journal of Public Health Midwifery), 2026)
Diabetic foot ulcer sare one of the chronic complication sof Diabetes Mellitus caused by micro circulation disorder sand peripheral neuropathy. They are characterized by chronic, non-healing wounds with a high risk of infection and potential amputation. Proper wound management is crucial for recovery. To apply nursing care in patients with diabetic ulcers using the moist wound healing method with Aloevera gel to improve skin tissue integrity. This study used a case study approach involving one patient treated at Public Health Center. The nursing process was implemented through five stages: assessment, nursing diagnosis, intervention, implementation, and evaluation. Interventions were carried out over five consecutive days, including wound care with Aloevera gel, peripheral perfusion monitoring, pain management, and patient education. Evaluation showed improvement in wound condition, increased granulation tissue, reduced slough and pain, and improved peripheral perfusion. Pain scale decreased from 4 to 2,and the patient was able to perform independent wound care. The application of moist wound healing using Aloevera gel is effective in improving skin tissue integrity and promoting patient self-care in managing diabetic ulcers. Structured and educational nursing interventions support the achievement of optimal nursing goals.